Renal Involvement in IPEX Syndrome With a Novel Mutation of FOXP3: A Case Report - Ke, Ruijuan; Zhu, Ying; Deng, Fang; Xu, Daliang (Frontiers in Genetics, 2022)
The immune dysregulation polyendocrinopathy enteropathy, X-linked syndrome (IPEX) is a rare genetic disease characterized by multiple immune disorders. The different mutations of FOXP3 gene may lead to different manifestations. Here we present a rare case of IPEX syndrome with a novel variant in FOXP3 gene. Clinical manifestations include autoimmune hemolysis, bronchiectasis, diarrhea, and proteinuria but not diabetes and other endocrine disorders. Whole-exon sequencing confirmed the diagnosis of IPEX syndrome. Supportive treatment did not ameliorate his symptoms and immunosuppressive therapy showed a promising efficacy. Our report would provide a reference for the diagnosis and treatment of IPEX syndrome.